2022
DOI: 10.3390/healthcare10030457
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Music Care on the Lived Experience of Isolation and Loneliness in Long-Term Care: A Qualitative Study

Abstract: This qualitative study aims to understand the lived experience of residents and other stakeholders during the implementation of a comprehensive music program in long-term care. It was conducted using a subset of 15 long-term care homes from the Room 217 Foundation Music Care Partners (MCP) “Grow” study in Ontario, Canada. The MCP program’s approach to music delivery uses therapeutic music practices such as “music care” to improve the care experience for caregivers and residents in long-term care homes. Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Other studies reported introducing therapeutic or leisure activities into nursing homes (n = 11), such as music-and art-based activities [51][52][53][54][55], intergenerational visiting programmes [56][57][58] and peer-mentoring [59][60][61]. The remaining articles described changes in the management, living arrangements and philosophy of care at nursing homes (n = 5), including a multi-componential strategy [62], a plan on how to design and execute an integrated intervention [63], the Eden Alternative programme [64] and reports on intergenerational living arrangements [65,66].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies reported introducing therapeutic or leisure activities into nursing homes (n = 11), such as music-and art-based activities [51][52][53][54][55], intergenerational visiting programmes [56][57][58] and peer-mentoring [59][60][61]. The remaining articles described changes in the management, living arrangements and philosophy of care at nursing homes (n = 5), including a multi-componential strategy [62], a plan on how to design and execute an integrated intervention [63], the Eden Alternative programme [64] and reports on intergenerational living arrangements [65,66].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…First, they referred to the quantity of social interactions. Thus, social isolation was seen as the objective lack of interactions [51], referring to the number of social contacts and interactions [53] or criticizing the lack of opportunities for nursing home residents to interact with each other or external actors [65]. The second dimension concerns the subjective perspective on interactions: Several studies claimed that loneliness occurs when individuals do not consider their existing interactions to be meaningful and fulfilling.…”
Section: Definition and Measurement Of Loneliness And Social Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have highlighted that music is always "music plus" (i.e., music plus people and things in action in context), and that music can reframe identities, provide pretexts for social relating and provide metaphors and subject matter for personal and group-historical narratives, among other things [37]. Studies on the impact of music engagement and participation on loneliness have given focus to older people in residential care settings and/or their caregivers [38][39][40], a demographic that has stereotypically been associated with loneliness [41], although recent research has found that younger people may be at higher risk [42]. Given that loneliness and social isolation are serious public health concerns, further research within and across disciplines is needed to examine how music may address loneliness and support people who are socially isolated.…”
Section: Introductionmentioning
confidence: 99%